THE ROLE OF THE GROUP ENVIRONMENT IN THE EVOLUTION OF GALAXIES: INVESTIGATING GROUP DYNAMICS AND PRE-PROCESSING - Hou, Annie (My University, 2013)
The influence of environment in galaxy evolution has been observed in a wide range of environments, where in general red quiescent early-type galaxies preferentially reside in high-density regions. The aim of this thesis is to understand the role that galaxy groups, and in particular group dynamics, play in galaxy evolution.
We examine substructure in rich groups at intermediate redshifts and find that 4/15 groups contain substructure, which is preferentially found on the group outskirts. Galaxies in groups with substructure have properties similar to the field, while the galaxies in groups with no substructure are similar to cluster populations. These results indicate that substructure galaxies do not feel the effects of the environment until well inside the group potential.
We then study the evolution of group dynamics to z~1 and find that the fraction of non-Gaussian groups increases with redshift, while the fraction of groups with substructure remains constant. Additionally, we find that the quiescent fraction correlates with galaxy stellar mass, but has little or no dependence on group dynamical mass or state. However, we do observe some correlation between substructure and quiescent fraction for low mass galaxies.
Finally, we investigate infalling subhalo galaxies to probe the importance of pre-processing in galaxy evolution. At r200 > 2, galaxies in subhaloes show enhanced quenching, when compared to non-subhalo galaxies. At these radii, the infall population dominates, indicating that enhanced quenching is due to the infalling subhalo population. Additionally, the fraction of groups with subhaloes is a function of halo mass, where more massive systems have a higher fraction of subhaloes. We conclude that for groups, pre-processing is insignificant; however, for the most massive clusters a significant fraction (∼ 25%) of the member galaxies have been pre-processed.
Keywords: Astronomy; galaxy evolution; galaxy groups; dynamics; External Galaxies; External Galaxies